Treatment with Sulodexide Downregulates Biomarkers for Endothelial Dysfunction in Convalescent COVID-19 Patients - Alejandro J Gonzalez-Ochoa MD; Gyozo Szolnoky MD; Ana G Hernandez-Ibarra MD; Jawed Fareed PhD (Clinical and Applied Thrombosis/Hemostasis)
Introduction Persistent elevation of biomarkers associated with endothelial dysfunction in convalescent COVID-19 patients has been linked to an increased risk of long-term cardiovascular complications, including long COVID syndrome. Sulodexide, known for its vascular endothelial affinity, has demonstrated pleiotropic protective properties. This study aims to evaluate the impact of sulodexide on serum levels of endothelial dysfunction biomarkers in patients during the convalescent phase of COVID-19. Methods We conducted a double-blind, single-center, randomized, placebo-controlled trial in Mexico, comparing sulodexide (250 LRU orally, twice daily) with placebo over 8 weeks in adult patients during early COVID-19 convalescence. Differences in serum biomarkers between the groups were analyzed using repeated measures and post hoc tests, with Thrombomodulin (TM) as the primary endpoint. Results Among 206 analyzed patients (103 in each group), at week 8, the sulodexide group exhibited significantly lower mean levels of Thrombomodulin (TM) (25.2 ± 7.9 ng/mL vs 29.9 ± 14.7 ng/mL, P  = .03), von Willebrand Factor (vWF) (232 ± 131 U/dL vs 266 ± 122 U/dL, P  = .02) and Interleukin-6 (IL-6) (12.5 ± 13.2 pg/mL vs 16.2 ± 16.5 pg/mL, P  = .03) compared to the placebo group. D-dimer and C reactive protein (CRP) in the sulodexide group were also lowered. No significant differences were observed for P-selectin, fibrinogen, VCAM-1, or ICAM-1 levels. Conclusions Patients in the convalescent phase of COVID-19 who received sulodexide for eight weeks showed a reduction in TM, vWF, D-dimer, CRP, and IL-6 serum levels compared to placebo. These findings suggest a potential protective effect of sulodexide against thromboinflammation and endothelial damage.